Birt-Hogg-Dubé syndrome - André Lencastre; Pedro Ponte; Margarida Apetato; Luis Nunes; Sara Lestre (Sociedade Brasileira de Dermatologia, 2013)
A 45-year-old woman with a history of renal carcinoma was observed for facial, cervical and truncal flesh-colored papules. Relatives had similar skin findings and a brother had repeated episodes of pneumothorax. The computerized tomography scan revealed multiple cysts on both lungs. A skin biopsy revealed a perifollicular fibroma. The clinical diagnosis of Birt-Hogg-Dubé syndrome (BHDS) was corroborated by identification of a novel frameshift c.573delGAinsT (p.G191fsX31) mutation in heterozygosity on exon 6 of the folliculin gene. The presence of multiple and typical benign hair follicle tumors highlights the role of the dermatologist in the diagnosis of this rare genodermatosis that is associated with an increased risk of renal cell cancer and pulmonary cysts, warranting personal and familial follow-up and counseling.